La indagación científica y la transmisión-recepción: una contrastación de modelos de enseñanza para el aprendizaje del concepto densidad - Florez-Nisperuza, Elvira Patricia; De la Ossa Albis, Andrés Fernando (Revista Científica, 2018)
The scientific inquiry has been the focus of multiples researches in the last decades, some support and others discredit its effectiveness in learning in relation to more traditional teaching models such as transmission-reception, that for this study, are integrated into laboratory practices consistent with the respective methodologies. The main objective of the research is to determine which of these teaching methodologies have the greatest influence in the learning of the concept of density as property of matter in the levels of knowledge, understanding, and implementation after the intervention of such strategy; inquiry in the experimental group and, transmission-reception in the control group, and, furthermore, characterize the levels of inquiry reached by the different teams formed to carry out the laboratory practices of the group subjected to said strategy and related it to learning. To achieve this is used the quantitative paradigm of investigation and a quasi-experimental design of transversal type with pre-and post-test. The results show conclusively that the scientific inquiry present best results in learning the concept in question, other than the methodology of contrast with an average of (10,59) and (8,18) respectively, statically corroborated by a test T that shows a significant level of 0,017. In addition, the laboratory team that presented the best level of inquiry also obtained the best average in the post-test, nevertheless, unlike the team with the lowest performance in the inquiry, exceeded the rest of the teams in said average.